Examining Macroeconomic variables on Credit risk in the South African Banking System - Mokatsanyane, Daniel; Stiglingh, Leonie (Acta Universitatis Danubius. Œconomica, 2023)
Abstract: Banks are the fundamental component of a country's financial system and are critical in supplying liquidity in a market economy. Therefore, banks, by the very nature of their existence and the crucial role they play in the financial landscape, are exposed to a variety of risks. Objectives the primary objective of this study was to employ quantitative research methods to analyze the relationship between credit risk and various macroeconomic variables. Previous Work this research builds up on studies that have confirmed the relationship between macroeconomic factors and credit risk. Approach Annual secondary macroeconomic and bank specific data variables from 2007-2022 was used to analyses the relations ship between the variables. Results the results of this study show a long-run relationship between credit risk and the observed macroeconomic variables, however only the GDP growth rate and exchange rate seem to influence credit risk when considered in the short run. Implications This study can be used by banks to check how other banks are performing and for academic researchers as a comparison to their own academic work Value this study adds to the existing knowledge of the variables that generate credit risk and highlights GDP and exchange rate to be factors to be variables banks should manage to help reduce credit risk.